(untitled) (Foro de Educacion, 2013)
The article seeks to present the philosophy of education that is at the very heart of William James’s legacy. It is argued that along with the rise of interest in the field of education towards classic American pragmatism, the study of William James has suffered from a lack of attention. After giving an accurate overview of the themes under debate in those few works which have addressed James’s thought from a pedagogical perspective, the article progresses on discussing some other educational themes which have gone unnoticed. More precisely, first, the inspiration offered by the image of the «tactful teacher» and, second, the philosophy of moral education that is part of James’s works on psychology. Both themes account for the pedagogical potential that continues to be hidden in the work of this philosopher.